THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND SPEAKING ABILITY - Nur Ayu Rijal; Syaiful Syaiful; Abdul Haris Sunubi; Nanning Nanning (STKIP Darud Da'wah Wal Irsyad Pinrang, 2025)
The aim of this study is to find out the correlation between students grammar mastery and students speaking ability the 5th semester of English Education Program at IAIN Parepare . This research was carried out from April to May 2022, the sample in this study was the students 5th semester at IAIN Parepare, totaling 20 students. This is part of a population of 85 students. The purpose of this study was to Is there correlation between students‟ grammar mastery and students speaking ability the 5th Semester of English Education Program at IAIN Parepare. The research used grammar mastery test and speaking ability test. The method used is correlation analysis with a survey approach, the calculation uses the product moment correlation formula. The result of data analysis that there is no significant correlation or weak correlation between grammar mastery (X) and speaking ability (Y) the students 3rd semester of English Education at IAIN Parepare. It can be seen from the correlation coefficient value between variable X and variable Y is 0,303, thus the variable can be categorized as a weak category at the index person product moment 0.20-0.399. Then the variable contribution between grammar mastery (X) and speaking ability (Y) was 9.18%.